Kaplan turbine working as a propeller: CFD investigation and experimental validation of generated power fluctuation. Issue 2 (March 2019) - Angulo, M; Rivetti, A; Lucino, C; Liscia, S
Abstract: Thanks to their ability to adjust automatically the guide vane and runner blades position, the use of Kaplan turbines is advantageous compared to other types in terms of power regulation, as a high efficiency can be attained over a wide range of head and power. However, such features have a cost of a more complex design of the components inside the hub and the main shaft. The number of daily movements of all these components, which is linked to the required power and frequency regulation, leads to wearing and fatigue in the long term. Therefore, the replacement and reparation of components are regular maintenance tasks which, on some occasions, might entail the dismantling of the turbine and the generator when some key hub components fails. In the face of such events, a cost-benefit-based decision must be made concerning to whether repair the turbine to recover its functionality or to operate the Kaplan turbine in propeller mode. In propeller mode, the turbine can operate at on-cam condition for a single load for any given head. For loads other than the corresponding to on-cam condition, an acceptable hydraulic behaviour is not guaranteed, since such use is usually not contemplated in acceptance tests. Therefore, pressure fluctuation due to vortex rope development, cavitation, power instability and structural vibration may arise at loads other than the corresponding to on cam operation. One of the main issues that limits the operation range is the generated power oscillation due to partial load vortex development. This paper presents numerical investigations focusing in this phenomenon. The computational domain includes guide vanes, runner and draft tube. Also, a simplified draft tube consisting in a symmetrical revolution volume is explored. Measurements were performed at prototype scale at same operating conditions and pressure fluctuations, power generation, vibrations and sound emission were recorded. These measurements are then shown and compared with CFD results.